Genetic homocysteine risk shapes cardiocerebral structure and multimorbidity through age- and sex-specific mechanisms: a UK Biobank study - Feng, Chenjie; Ma, Yupeng; Zhang, Tian; Zhang, Peng; Zhao, Yu (Frontiers in Nutrition, 2025)
BackgroundElevated homocysteine (Hcy) levels have been implicated in cardiometabolic and neurological disorders. However, the age- and sex-specific mechanisms by which genetically determined Hcy levels contribute to disease risk via structural alterations in the heart and brain remain unclear.MethodsWe analyzed data from 306,796 UK Biobank participants. A weighted polygenic risk score (PRS) for Hcy was constructed and tested for associations with cardiovascular and neuroimaging phenotypes. Mediation analyses assessed the extent to which these structural traits mediated disease risk. We also examined whether two dietary patterns—the sulfur microbial diet and the EAT-Lancet diet—modulated Hcy levels or disease associations.ResultsGenetically elevated Hcy was significantly associated with sex- and age- specific alterations in brain white matter and cardiac structure. These structural traits partially mediated the link between Hcy and hypertension, dyslipidemia, and cognitive impairment. Surprisingly, neither dietary index was associated with Hcy levels, although both showed independent associations with disease risk.ConclusionOur findings suggest that genetically determined Hcy levels impact cardiocerebral structure in a sex- and age-dependent manner, contributing to disease risk. Structural imaging phenotypes offer potential as early mediators. The dietary effects on disease risk may involve pathways independent of Hcy modulation.